Entrepreneurship and development in the 21st century - Sergi, Bruno S.; Scanlon, Cole C., 1996- (Lab for entrepreneurship and development, 2019)
The 21st century has brought about new trends in entrepreneurship and development. In this insightful volume, a cast of expert contributors explore how these new trends, along with a variety of political, cultural and social influences, have affected entrepreneurship, in all of its manifestations.